Chlorin e6 Conjugated Interleukin-6 Receptor Aptamers Selectively Kill Target Cells Upon Irradiation - Sven Kruspe; Cindy Meyer; Ulrich Hahn (Elsevier, 2014)
Photodynamic therapy (PDT) uses the therapeutic properties of light in combination with certain chemicals, called photosensitizers, to successfully treat brain, breast, prostate, and skin cancers. To improve PDT, current research focuses on the development of photosensitizers to specifically target cancer cells. In the past few years, aptamers have been developed to directly deliver cargo molecules into target cells. We conjugated the photosensitizer chlorin e6 (ce6) with a human interleukin-6 receptor (IL-6R) binding RNA aptamer, AIR-3A yielding AIR-3A-ce6 for application in high efficient PDT. AIR-3A-ce6 was rapidly and specifically internalized by IL-6R presenting (IL-6R+) cells. Upon light irradiation, targeted cells were selectively killed, while free ce6 did not show any toxic effect. Cells lacking the IL-6R were also not affected by AIR-3A-ce6. With this approach, we improved the target specificity of ce6-mediated PDT. In the future, other tumor-specific aptamers might be used to selectively localize photosensitizers into cells of interest and improve the efficacy and specificity of PDT in cancer and other diseases.